Estrutura populacional e tendências genética e fenotípica da raça Guzerá criada no Nordeste do Brasil - Santos, Leonardo Hunaldo dos (2008)
This research was carried out to assess genetically the breed Zebu Guzera beef cattle in Northeast of Brazil, borned between 1976 and 2007, through the estimation of genetic parameters for 205 (W205), 365 (W365) and 550 (W550) days of age, behavior analysis of the trend lines of genetic, phenotypic and environmental and interrelationship of population structure with genetic progress. The components of (co)variance were obtained by the method of restricted maximum likelihood using the computer program MTDFREML. The model used for the W205 include random genetic effects, direct and maternal, and permanent environment, beyond the fixed effect of contemporary group. For W365 and W550, they were considered fixed effects, however, only the direct genetic effect as random effect. The trend estimate genetic, phenotypic and environmental characteristics were obtained for the linear regression weighted average of the dependent variable (genetic values, weights and solution of the observed GC on the year of birth. The ENDOG program was used for the analysis of pedigree and parameters estimation based on the probability of gene origin, effective size (Ne), generation interval and coefficient of inbreeding. Direct heritability were estimated equal to 0.11 ± 0.02 (W205), 0.18 ± 0.02 (W365) and 0.18 ± 0.02 (W550). The maternal heritability for W205 was to 0.01 ± 0.02. The genetic trend for direct W205, significant (p<0.01) and equal to 0.0094 kg/year, while the maternal genetic trend was significant (p <0.01) and equal to -0.0013 kg/year. W365 and W550 showed highly significant direct genetic trends (p <0.001) and equal to 0.0214 kg/year and 0.0255 kg/year, respectively. The phenotypic and environmental trends were highly significant (p <0.001) and respectively: 1.6584 and 1.6287 (W205), 2.0829 and 2.0175 (W365), 3.3364 and 3.2237 (W550) kg/year. The intervals of generations: 7.5±4.5 (Father-Son), 7.9±3.9 (Father-Son), 7.8±4.2 (Mother-Son), 7,9 ±4.8 (Mother-Daughter),with a mean interval of 7.9 ± 4.4 years. The effective size has increased between the periods 1976-78 to 1986-90 from 240% to reach 674. Then there was a reduction of 110% reaching 318 in 1994, from which there was another rise, reaching 532 in 2006. The inbreeding coefficient showed the greatest growth from the second to the seventh generation, when increased from 0.17% to 2.06%, however, the average inbreeding in inbred animals decreased from 15.66% to 6.75% during the same period. There is low possibility to select the animals for the W205 due to low heritability, however, W365 and W550 showed moderate heritability, presenting opportunity for gain. The significantly gains should be attributed to improvements in the environment. The effective size is great and the population has no risk of extinction. The ranges of generation were high, which caused losses genetic. The use of young bulls evaluated for a limited time can provide reduction in the intervals of generation and increases in genetic gains